PERAN KUALITAS PELAYANAN, KEPERCAYAAN DAN KEMUDAHAN PENGGUNAAN TERHADAP KEPUASAN KONSUMEN SHOPEE - Muqodasih, Layni Darul; indriastuti, ariyani (Sekolah Tinggi Ilmu Ekonomi Semarang, 2023)
Abstract. Properly managing and understanding the relationship between service quality, trust, and ease of use is the key to creating a positive customer experience and creating consumer satisfaction. This research aims to determine the influence of service quality, trust, and ease of use on consumer satisfaction. The sampling method uses accidental sampling with a sample size of 100 respondents. The data collection method uses a questionnaire. The analysis tool uses multiple linear regression tests. The research results show that service quality and user friendliness have a significant effect on Shopee consumer satisfaction. The trust variable does not have a significant effect on Shopee consumer satisfaction.